Preoperative evaluation of geriatric patients undergoing liver transplantation. Issue 1 (7th February 2022) - Akhtar, Shamsuddin
Abstract : Purpose of review: As the population of the world is aging the number of geriatric patients undergoing liver transplantation (LT) is also increasing. They pose a unique challenge for the caregivers, as they have age-related physiological changes, multiple comorbidities and cirrhosis-related pathologies. Recent findings: Twenty-two percent of patients who undergo LT are older than 65 years. Many patients suffer from nonalcoholic steatohepatitis (NASH), hepatocellular carcinoma and hepatitis-C virus. Incidence of NASH tends to increase with age, obesity, diabetes and metabolic syndrome. Elderly patients require comprehensive cognitive, cardiac and pulmonary evaluation prior to LT. Cirrhotic cardiomyopathy, hepatopulmonary syndrome, portopulmonary hypertension and frailty are of specific concern. Summary: Proportion of elderly patients who are undergoing LT continues to increase. These patients require comprehensive cardiopulmonary and frailty evaluation. Consensus-based practice advisories need to be developed to standardize preoperative evaluation of geriatric patients awaiting LT.